Wear and Corrosion Resistance of FeCoCrxNiAl High-Entropy Alloy Coatings Fabricated by Laser Cladding on Q345 Welded Joint - Qiang Ben; Yumeng Zhang; Longxiang Sun; Leilei Wang; Yanni Wang; Xiaohong Zhan (Metals, 2022)
High-entropy alloy (HEA) coatings on the surface of low-alloy steel by laser cladding can improve the corrosion and wear resistance, and the performance can be further improved by adding the Cr element. However, the effect of Cr content on the microstructure, hardness, wear and corrosion resistance of the coatings on the welded joint has not been completely understood in the literature. This paper aims at revealing the influence of Cr content on the microstructure and properties of laser-cladded FeCoCrxNiAl HEA on different regions of Q345 welded structure. The results indicate that FeCoCrxNiAl HEA coating has good metallurgical bonding with the Q345 welded surface. The increase of Cr element content in the powder plays an important role in energy absorption of powder and substrate, affecting the dilution rate and diffusion of Fe from the substrate to HEA coating. The HEA coating is mainly composed of the face-centered cubic phase (FCC) and body-centered cubic phase (BCC). When x = 1.5, the actual Cr element content of coating is the highest, which promotes the formation of hard brittle phase BCC, and subsequently affects the hardness and wear resistance of the sample. Meanwhile, the corrosion resistance increases and then decreases, and reaches the highest when x = 1.5. Due to the existence of Cr and other elements with good corrosion resistance in the HEA coating, a dense oxide film can be formed in 3.5 wt.% NaCl solution and neutral salt spray environment to prevent the corrosion from continuing, which can effectively improve the corrosion resistance of each region of the welded joint, and the protective efficiencies on the weld bead (WB), heat-affected zone (HAZ) and base metal (BM) are 99.1, 98.4 and 96.6%, respectively.